Ovarian Cancer: Current Scenario, Treatment And Novel Strategies For Management - Suthar, Shreya; Desai, Shryas (Asian Journal of Pharmaceutical Research and Development, 2020)
Ovarian cancer is the leading gynaecological cancer among women globally and leads to death with 5-year survival rate of metastatic form of ovarian cancer as only 20-30%. Detection of disease at an early stage is very difficult and no screening test are available for detection of OC in general population. For effective management of ovarian cancer chemotherapy, surgery, hormone therapy and radiation therapy are often used alone or in combination depending on the stage and severity of ovarian cancer. This mini-review describes about facts and figures as well as current diagnosis and treatment methods available for ovarian cancer. The manuscript will also cover a brief description of recent research of developing novel strategies such as liposomal drug delivery carriers in management of cancer.